Decisions about palliative care and social determinants of health in intensive care units: a scoping review - Hyeyoung Yun; Jung Yeon Kim; Eugene Han; Yeonsoo Jang (Acute and Critical Care, 2026)
Social determinants of health (SDoH) play important roles not only in a patient's health status but also in access to palliative care, the family's decision-making process, and the formation of patient values and preferences. In this scoping review, we analyze the social determinants that influence palliative care decision-making and examine the relationship between palliative care decisions and SDoH in the intensive care unit (ICU). We conducted a literature search of five databases including the search terms “Intensive care units,” “palliative care,” and “social determinants of health.” The search was limited to English publications from January 2015 to March 2025. Out of a total of 3,575 studies, we selected 20 for further review. Of those 20 studies, some reported that SDoH such as age, race, financial status, religion, sex, region or country, education level, and language proficiency affected decisions regarding ICU palliative care and whether to discontinue life support treatment. The reviewed studies of SDoH-related palliative care in the ICUs focused on aspects of palliative care associated with treatment withholding and withdrawing life support treatment. This study underscores the importance of integrating SDoH with clinical indicators in decision-making processes for palliative care in the ICU. Although establishing definitive relationships between SDoH and ICU palliative care decisions remains challenging, our findings highlight the potential impacts of social factors on care planning. Further research across various clinical settings is essential to clarify this relationship to develop more comprehensive and equitable palliative care strategies.